New Light on Dark Extended Lenses with the Roman Space Telescope - William DeRocco; Nolan Smyth; Volodymyr Takhistov (The Astrophysical Journal Letters, 2024)
The Roman Space Telescope’s Galactic Bulge Time Domain Survey will constitute the most sensitive microlensing survey of the Galactic bulge to date, opening up new opportunities to search for dark matter (DM). Many extensions of the Standard Model predict the formation of extended DM substructures, such as DM subhalos, boson/axion stars, and halo-dressed primordial black holes. We demonstrate that for such targets, Roman will be sensitive to a broad parameter space up to 4 orders of magnitude below existing constraints. Our analysis can be readily applied to other extended DM configurations as well.